Pelatihan Peningkatan Pemahaman Perwasitan Cabang Olahraga Petanque Timor Leste dan Indonesia di Surabaya - Suryanto Agung Prabowo; Dwi Cahyo Kartiko; Abdul Rachman Syam Tuasikal; Shidqi Hamdi Pratama Putera; Bayu Budi Prakoso; Bayu Ristiawan; Diva Ristie Valentina; Yogiswara Anugrah Pamungkas; Muhammad Fauzi Antoni; Novadri Ayubi (Jurnal Kabar Masyarakat, 2026)
This community service program aimed to improve the understanding and officiating skills in the sport of petanque in Timor Leste. The main problems faced by the partner included low technical knowledge of officiating, limited competent human resources, and the absence of a structured and sustainable officiating development system. The method used was competency-based training consisting of theoretical instruction, case study discussions, simulations, and field practice using an experiential learning approach. Evaluation was conducted using pre-test and post-test instruments, with data analyzed through the Wilcoxon test to measure participants’ improvement. The results showed a significant increase in knowledge, with the mean score rising from 1.85 to 4.10, and in skills, from 1.90 to 4.00, with a significance value of p < 0.05. Additionally, participant satisfaction reached a very good category (91%). This program proved effective in enhancing officiating competence and contributed to the development of a more professional and sustainable officiating system in Timor Leste.